Methods of Improving Technical Training of Belt Wrestlers (Texas Journal of Multidisciplinary Studies, 2022)
In this research paper, the role of the quality of flexibility in the training and development of belt wrestlers in technical movements in the competition process and the effective scientific basis are given.